2006
DOI: 10.1136/gut.2005.066100
|View full text |Cite
|
Sign up to set email alerts
|

Specific probiotic therapy attenuates antibiotic induced visceral hypersensitivity in mice

Abstract: Perturbations in gut flora and in inflammatory cell activity alter sensory neurotransmitter content in the colon, and result in altered visceral perception. Changes in gut flora may be a basis for the variability of abdominal symptoms observed in functional gastrointestinal disorders and may be prevented by specific probiotic administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
318
3
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(336 citation statements)
references
References 36 publications
9
318
3
6
Order By: Relevance
“…A study in rats demonstrated that Lactobacillus reuteri can inhibit visceral pain through effects on enteric nerves. 58 Moreover, Verdu et al 59,60 have shown in two murine models that Lactobacillus paracasei normalizes visceral hypersensitivity and postinfective muscle hypercontractility. Lactobacillus reuteri is, nonetheless, the only strain in these mechanistic studies that has been investigated in a clinical trial, as well and in this case without success.…”
Section: Discussionmentioning
confidence: 99%
“…A study in rats demonstrated that Lactobacillus reuteri can inhibit visceral pain through effects on enteric nerves. 58 Moreover, Verdu et al 59,60 have shown in two murine models that Lactobacillus paracasei normalizes visceral hypersensitivity and postinfective muscle hypercontractility. Lactobacillus reuteri is, nonetheless, the only strain in these mechanistic studies that has been investigated in a clinical trial, as well and in this case without success.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the composition of GI commensals have been demonstrated in patients with IBS [Kassinen et al 2007;Malinen et al 2005]. Murine studies have demonstrated a reduction in visceral hypersensitivity [Verdu et al 2006], and attenuation of postinfectious muscle hypercontractility [Verdu et al 2004], following administration of probiotics. They may also have an influence on the host immune response to infection, as indicated by a reduction in circulating cytokine levels [O'Mahony et al 2005].…”
Section: Probioticsmentioning
confidence: 99%
“…Yet the effects on intrinsic enteric neurons are largely unexplored. Feeding with certain bacterial species and strains reduces the perception of visceral pain [3][4][5][6] , decreases activity in spinal single afferent fibres 4 and inhibits colorectal distension induced sensitization of dorsal root ganglion neurons 7 . Ingestion of a Lactobacillus rhamnosus strain, 'JB-1', (ref.…”
mentioning
confidence: 99%